Financial literacy of digital citizens in the metaverse: Reality or fiction? - Yuri A. Bokov; Svetlana M. Mironova; Maxim S. Sitnikov (RUDN Journal of Law)
The global trend of digitalization is giving rise to new institutions and rethinking established ones within the state and society. In this context, studying individual objects in their symbiosis is both effective and justified. Scholars are increasingly focusing on the potential existence of digital citizenship within the emerging metaverses with early examples found in South Korea. The authors of the paper believe that scientific thought may extend even further. One premise for creating metaverses involves the development of the economic component, reflected in the movement of cash flows within the virtual space. Today, the primary users of metaverse prototypes are Generation Z (Zet) and A (Alpha), who require special state protection from harmful financial content due to their naivety. Therefore, the purpose of this study is to conduct a comprehensive SWOT analysis of the necessity and potential for enhancing the financial literacy of digital citizens in metaverses, particularly within the Russian context. Methodology: The principal method used in this study is formal legal analysis, which reveals the normative basis for implementing digital citizenship, metaverses, citizenship, and financial literacy. The findings are based, inter alia, on an analysis of regulatory legislation. Using a systemic approach, the authors present the theoretical and regulatory frameworks as well as practical implementations of categories related to digital citizenship, metaverses, citizenship, and financial literacy as a complex system with various interrelated components. As a result of this study, a Russian model for increasing the financial literacy of digital citizens in the metaverse has been proposed and substantiated, alongside the identification of several legal risks in this area.